The minimization of mechanical work in vibrated granular matter - Clewett, James P.D.; Wade, Jack; Bowley, R.M.; Herminghaus, Stephan; Swift, Michael R.; Mazza, Marco G. (Nature Publishing Group, 2016)
Experiments and computer simulations are carried out to investigate phase separation in a granular gas under vibration. The densities of the dilute and the dense phase are found to follow a lever rule and obey an equation of state. Here we show that the Maxwell equal-areas construction predicts the coexisting pressure and binodal densities remarkably well, even though the system is far from thermal equilibrium. This construction can be linked to the minimization of mechanical work associated with density fluctuations without invoking any concept related to equilibrium-like free energies.